2020
DOI: 10.1111/os.12610
|View full text |Cite
|
Sign up to set email alerts
|

Total Knee Arthroplasty in Patients with Prior Femoral and Tibial Fractures: Outcomes and Risk Factors for Surgical Site Complications and Reoperations

Abstract: Objective To investigate the outcomes of total knee arthroplasty (TKA) in patients with a prior femoral or tibial fracture, and identify the risk factors for surgical site complications and reoperations. Methods Seventy‐one TKAs performed in 71 patients with a prior tibial or femoral fracture between January 2005 and December 2016 were reviewed retrospectively. Forty males (40 knees) and 31 females (31 knees) were included. The mean age at the time of TKA was 59.2 (range, 29–83) years. Outcomes were assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…Another potential explanation may be that younger patients are more likely to have IA (e.g., rheumatoid arthritis) or SOA (e.g., post‐traumatic arthritis) rather than POA. These indications for TKA which were also detected as risk factors of PRCs in this study may be associated either with poor immune response (e.g., corticosteroid therapy) or with multiple prior surgeries (e.g., arthrotomy with open reduction and internal fixation of the traumatic injury) that increase risk of PJI or PPF 1,5,12,23,25,27,33 . Considering the context that TKA will be performed more frequently in younger patients, this finding suggests a demand for continued efforts to optimize outcomes in this population.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Another potential explanation may be that younger patients are more likely to have IA (e.g., rheumatoid arthritis) or SOA (e.g., post‐traumatic arthritis) rather than POA. These indications for TKA which were also detected as risk factors of PRCs in this study may be associated either with poor immune response (e.g., corticosteroid therapy) or with multiple prior surgeries (e.g., arthrotomy with open reduction and internal fixation of the traumatic injury) that increase risk of PJI or PPF 1,5,12,23,25,27,33 . Considering the context that TKA will be performed more frequently in younger patients, this finding suggests a demand for continued efforts to optimize outcomes in this population.…”
Section: Discussionmentioning
confidence: 55%
“…These indications for TKA which were also detected as risk factors of PRCs in this study may be associated either with poor immune response (e.g., corticosteroid therapy) or with multiple prior surgeries (e.g., arthrotomy with open reduction and except for the miscellaneous (0.43%), periprosthetic joint infection (0.20%) is the most common PRCs, followed by mechanical loosening (0.04%), dislocation (0.02%), and periprosthetic fracture (0.01%). internal fixation of the traumatic injury) that increase risk of PJI or PPF 1,5,12,23,25,27,33 . Considering the context that TKA will be performed more frequently in younger patients, this finding suggests a demand for continued efforts to optimize outcomes in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Despite relatively inferior outcomes as compared with primary OA knee, TKA remains the treatment of choice in these patients. 12,15,20 On the other hand, results still can be promising if the factors are addressed with elegance while performing TKA. 21 The surgical dilemma in these cases is whether to remove or retain the hardware.…”
Section: Discussionmentioning
confidence: 99%
“…Phillips et al [11] showed that the incidence of symptoms of mild arthritis of the lower limb knee joint in patients with femoral fracture malunion and malalignment was signi cantly higher than that in the healthy side, and more obvious symptoms of traumatic arthritis (TA) of the knee joint may occur in long-term follow-up [12]. Nonunion or malunion of fractures can disrupt normal joint movement, leading to non-physiological stress and TA of the knee [13][14].…”
Section: Introductionmentioning
confidence: 99%